Antimicrobial and Antioxidant effect of Ficaria verna Huds. - Şule İNCİ; Ayşe EREN; Sevda KIRBAĞ; Ahmet İsmail ÖZKAN (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
Ficaria verna Huds. is a plant belonging to the Ranunculaceae family, known as mole grass and celandine among the people. It is known to have anti-inflammatory and anti-haemorrhagic pharmaceutical effects. In this study, it was aimed to determine the antimicrobial effect of different concentrations of F. verna extracts obtained from methanol, ethanol and chloroform and the antioxidant activity of different concentrations of the extract obtained from methanol. In the results obtained, the best antimicrobial effect (17-20 mm) against Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Bacillus megaterium, Salmonella thypii and Candida albicans was determined in the methanol extract of F. verna at a concentration of 1000 µg. It was observed that the scavenging effect of the DPPH radical of F. verna increased depending on increasing concentrations.